ASSESSMENT OF DEPRESSION AMONG UNIVERSITY STUDENTS USING PATIENT HEALTH QUESTIONNAIRE - Syeda Rizwana Jafri; Uzma Waseem; Hafsa Nazeer; Amna Muneeb; Muhammad Bilal Afzal; Khansa Qadir (Pakistan Armed Forces Medical Journal, 2020)
Objective: To determine prevalence of depression among university students in Pakistan according to patient health questionnaire.